The Role of International Atomic Energy Agency (IAEA) in Japan's Fukushima Treated Water Release Policy - Alena Alenka; Deasy Silvya Sari; Darmansjah Djumala (Green Publisher Indonesia, 2025)
Japan's policy of releasing treated water from the Fukushima Daiichi Nuclear Power Plant has sparked a global debate over its environmental safety and legitimacy. This issue is not only about the technical aspects of radioactive waste management but also reflects the dynamics of the relationship between science, politics, and international belief. This study aims to analyze the role of the International Atomic Energy Agency (IAEA) in supervising and verifying Japanese policies through the framework of institutional neoliberalism and the classification of the role of international organizations according to Clive Archer. Using a qualitative approach based on an analysis of official documents, IAEA submissions, and related stakeholder responses, the study found that the IAEA plays a role in three main categories: as an instrument, Japan uses the IAEA to gain scientific legitimacy; as an arena, this organization becomes a space for diplomacy between international actors and the exchange of technical information; and as an actor, the IAEA demonstrates autonomous capacity through the establishment of scientific safety standards and the production of global legitimacy. Although the IAEA report guarantees the safety of the Fukushima wastewater release, the responses of China, South Korea, and Pacific nations reflect a disconnect between scientific and moral legitimacy. Thus, this study confirms that the success of international organizations such as the IAEA depends on their ability to build cross-border trust and sensitivity to global values.